DAYA SAING KOMODITI KOPRA DI KABUPATEN MINAHASA SELATAN - Paulus A. Pangemanan; Yolanda P.I. Rori (AGRI-SOSIOEKONOMI, 2017)
This study aims to determine the competitiveness of kopra in the South Minahasa based competitive advantage and comparative advantage. The benefits of this research are as reference material to South Minahasa regency government in formulating policies related to commodities kopra. Data used include primary data and secondary data. The primary data collection conducted by interviewing farmers, especially farmers kopra. While secondary data taken from the agencies involved in this study as the Central Bureau of Statistics, department of agriculture and plantations, and the service industry and trade. Determining the location of this research was done by using purposive sampling, where the number of samples is set at 10 samples in the village Pakuure 2 with the consideration that the village is a producer of kopra in the South Minahasa District of Tenga. The analysis used in this research that the Policy Analysis Matrix (PAM). The results showed that the coefficient of the ratio of the cost of domestic resource (DRCR) is smaller than one that is 0.660 which means it can compete to be the leading export commodities in the international trade market, while the value of the coefficient ratio of private costs (PCR) commodities kopra smaller than one that is 0,249 which means it can compete in terms of quality and price.